THE ESSENCE OF MEANS OF EVIDENCE IN CRIMINAL PROCEEDINGS (Bulletin of criminological association of Ukraine, 2024)
In this article, it has been emphasized that on the pages of professional scientific literature, the main attention is paid to clarifying the general principles of criminal procedural evidence, as well as determining the criteria and standards for collecting, verifying and evaluating evidence from the standpoint of its relevance, reliability, admissibility and sufficiency. However, unjustifiably little attention is paid by both scientists and practitioners to the issue of means of evidence, in particular, determining their essence. It has been substantiated that means of evidence are an integral element of criminal procedural evidence in criminal proceedings. It has been emphasized that means of evidence and evidence in criminal proceedings have common features that indicate and at the same time determine their interdependence. It has been established that evidence in criminal proceedings is characterized by a number of features that, in their entirety, determine its essence, meaning and place in criminal procedural activity: clear criminal procedural regulation; correlation with international legal standards; carried out exclusively by authorized subjects; symbiosis of intellectual and procedural activity; cognitive nature; focus on establishing circumstances that are subject to proof and are important for criminal proceedings; carried out only within the framework of criminal proceedings and with the help of procedural instruments. It has been found that the means of evidence in criminal proceedings are tools for obtaining, verifying and evaluating evidence during pre-trial investigation and trial. The main features of the means of evidence in criminal proceedings have been identified, which in their entirety determine their essence, are: regulation by criminal procedural legislation of the grounds and the procedure for their use; aimed at establishing circumstances that are subject toproof and are important for criminal proceedings, as well as motivating the adoption of procedural decisions and arguing legal positions on procedural issues; compliance with international legal standards; used exclusively by authorized entities during criminal proceedings.
Keywords: evidence; means of proof; criminal proceedings; cognition; essence; signs